Conductive cyclized polyacrylonitrile coated LiNi0.6Co0.2Mn0.2O2 cathode with the enhanced electrochemical performance for Li-Ion batteries. (1st February 2020) - Huang, Yong; Xia, Jin; Hu, Guorong; Cao, Yanbing; Peng, Zhongdong; Fan, Ju; Tao, Yong; Li, Tianfan; Zhang, Zhiyong; Xue, Zhichen; Du, Ke
Abstract: Improving the cycling stability of LiNi0.6 Co0.2 Mn0.2 O2 at high voltage and high temperature has always been one of the critical directions for researchers to seek a breakthrough. In this study, a surface modification for LiNi0.6 Co0.2 Mn0.2 O2 materials by coating with the conductive cyclized polyacrylonitrile (cPAN) is employed. The cyclized polyacrylonitrile formed by heat treatment of polyacrylonitrile is confirmed to have delocalized π bonds and therefore has good electronic conductivity. The polyacrylonitrile not involved in the reaction is expected to leave the coating with a certain ionic conductivity. The conductive coating layer enhances the rate of electron exchange and ion exchange of the electrodes. Besides, the cyclized polyacrylonitrile with elasticity not only suppresses the volume expansion of the host materials but also plays a central role in suppressing electrochemical polarization by providing a barrier to suppress the interfacial reactions and electrolyte decomposition. The results show that the rate performance and cycling stability of LiNi0.6 Co0.6 Mn0.6 O2 at high voltage and high temperature are greatly improved by the surface modification.